Endoscopy-assisted removal of angle foreign body presenting as persistent localised corneal oedema - Nukala, Naveen (BMJ Case Rep, 2020)
A 20-year-old man presented to us with injury to the left eye by a glass bulb 3 weeks ago. The acute injury resolved with a peculiar residual localised corneal oedema in the inferior one-third of the cornea. This localised oedema in absence of any evidence of a localised visible injury to the cornea indicated towards a possible retained foreign body. The foreign body visibility was equivocal on gonioscopy. Subsequently via a limbal incision, an endoscope was introduced into the anterior chamber. The endoscopic view revealed the glass foreign body lodged into the inferior angle of the eye which was removed with the help of an intraocular forceps. Over the next week, the corneal oedema resolved completely.